The fast globalizing gendered construction of teacher education: A critical feminist research policy analysis of the contemporary reform movement - Mooney Simmie, Geraldine (Frontiers in Education, 2023)
Gendered narratives of teacher education often rely on research studies revealing the living contradictions of practice in a fast globalising educational reform ensemble. Here I argue that it is equally important for women in the academy of teacher education to conduct critical feminist research into the gendered construction of teacher education in macro policy landscapes in order to reveal, challenge and change the hegemonic masculinities at play in higher education in contemporary times. In this study, I conduct a critical scrutiny of this macro policy problem, the structures, strictures and cultural symbols that increasingly contain the gendered construction of teacher education in a confined ecosystem in higher education imbued with patriarchy and an elite conservativism. The critical feminist discourse analysis of two OECD policy documents in relation to gender justice shows that the gendered construction of teacher education in the fast globalizing reform ensemble fails to trouble a new consciousness for egalitarian gendered relations while constraints and failures can be explained, if not fully, by the privileging of hegemonic masculinities in the framing of teacher education at a macro policy level. My argument is centred on a reflexive view of teacher education as an academic study of human development and change that needs to foreground egalitarian gender relations for emancipatory and transformative practices that can offer hope and solidarity in ways that inspire deep learning and deep democracy.